Paraquat lung: a reappraisal - Smith, Paul (1974)
Smith, P. and Heath, D. (1974).Thorax, 29, 643-653. Paraquat lung: a reappraisal. The histopathology of the lungs from four human cases of paraquat poisoning is described. In two of them there was a dense mass of fibroblastic tissue which obliterated the lung architecture, and one of these showed an extensive deposit of collagen with honeycomb change. In a third case pulmonary fibrosis was less severe and could be demonstrated exclusively within the alveolar spaces. The fourth showed earlier lesions of capillary congestion, alveolar oedema, and hyaline membrane formation. We suggest that paraquat produces the same effect on the lung in man as in the rat, namely a diffuse, cellular, intra-alveolar fibrosis. The intra-alveolar origin of this fibrosis is often obscured in the advanced stage of the disease and has been misinterpreted as fibrosing alveolitis. This fibrosis is associated with a pulmonary vascular disease. In assessing the histopathology of the lung in paraquat poisoning a history of oxygen therapy must be taken into account, for prolonged exposure to this gas may in itself induce pulmonary fibrosis.